Pengembangan Bahan Ajar Tematik Pendamping Guru dengan Model Webbed untuk Sekolah Dasar Kelas 2 - Eka Wahyuni; I Nyoman Sudana Degeng; Nurmida Catherine Sitompul (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2018)
Implementation of the 2013 curriculum in elementary schools is applied using a thematic approach. The provision of teaching materials for teachers is one aspect that must be fulfilled by the government and it is still inadequate. This study aims to develop thematic teaching materials for teacher companion with a webbed model. The procedure for developing teaching materials uses the ADDIE development model which includes five stages, namely: analysis, design, development, implementation, and evaluation. The thematic model used to design teaching materials is the Spider Web Model or the Webbed Model. The data collected aims to see the feasibility of the product as teaching material and field trials in the learning class. The questionnaire data came from content / material experts, media experts, design experts, colleagues, and 24 students. The data analysis technique is descriptive. The results of the review of the feasibility of development products are as follows: 1) Review of Indonesian language education content / material experts by 95%, review of mathematics education experts by 98%, reviews of learning media experts state the suitability of the media used by development, and reviews of instructional design experts by 85% . Product trials with students and student responses through questionnaires get very good responses. So it can be concluded that the product that has been developed is suitable for use as a teacher companion book in teaching. Suggestions for using this product are that educators develop innovative ideas so that various themes can be developed according to student needs and the availability of a learning environment at school. This teaching material product can be used as an example for educators to develop their own teaching materials.